Exploiting interkingdom interactions for development of small-molecule inhibitors of Candida albicans biofilm formation - Reen, F.; Phelan, J.; Gallagher, L.; Woods, D.; Shanahan, R.; Cano, R.; Muimhneacháin, E.; McGlacken, G.; O'Gara, Fergal (American Society for Microbiology, 2016)
© 2016, American Society for Microbiology. All Rights Reserved. A rapid decline in the development of new antimicrobial therapeutics has coincided with the emergence of new and more aggressive multidrug-resistant pathogens. Pathogens are protected from antibiotic activity by their ability to enter an aggregative biofilm state. Therefore, disrupting this process in pathogens is a key strategy for the development of next-generation antimicrobials. Here, we present a suite of compounds, based on the Pseudomonas aeruginosa 2-heptyl-4(1H)-quinolone (HHQ) core quinolone interkingdom signal structure, that exhibit noncytotoxic antibiofilm activity toward the fungal pathogen Candida albicans. In addition to providing new insights into what is a clinically important bacterium-fungus interaction, the capacity to modularize the functionality of the quinolone signals is an important advance in harnessing the therapeutic potential of signaling molecules in general. This provides a platform for the development of potent next-generation small-molecule therapeutics targeting clinically relevant fungal pathogens.